ROZPORZĄDZENIE PREZYDENTA RP Z 19 STYCZNIA 1928 R. O ORGANIZACJI I ZAKRESIE DZIAŁANIA WŁADZ ADMINISTRACJI OGÓLNEJ – PRZEŁOM W BUDOWIE USTROJU ADMINISTRACYJNEGO PAŃSTWA POLSKIEGO DOBY MIĘDZYWOJENNEJ - Gałędek, Michał (Zeszyty Prawnicze, 2016)
THE PRESIDENTIAL DECREE OF 19. JANUARY 1928 CONCERNING THE ORGANIZATION AND OPERATION OF GENERAL ADMINISTRATION – A BREAKTHROUGH IN THE PROCESS OF THE CONSTRUCTION OF THE ADMINISTRATIVE SYSTEM IN THE INTERWAR PERIOD Summary Presidential Decree governing organization and operation of local administration performed in the interwar period a numer of important functions. It consolidated the existing system due to the separateness of the period of Poland’s partition, basing it on a uniform rules. This act ordered administrative organization, clarified many of the solutions (already adopted but not developed) as well as strengthened the legal position of provincial governor (voivode) as the most important local authority. For all these reasons, Presidential Decree no doubt was a major breakthrough in the construction of Polish local administration.